The 2030 Agenda for Sustainable Development and China's implementation. Issue 2 (3rd April 2017) - Zhu, Jing
ABSTRACT: The concept of sustainable development has experienced great development and change at different levels of theoretical connotation and practical implementation since 1960s and 1970s when it was first proposed. People's understanding of the relationship between economy, society, and environment has been continuously deepened over the years. When it came to the end of 2015, it is necessary to examine the results of the United Nations Millennium Development Goals on sustainable development, and at the same time, the post-2015 framework and guidance on sustainable development at the global level were to be made, including the ideas, action plans, key areas that would guide the global sustainable development. The 2030 Agenda for Sustainable Development has developed a 5P theoretical framework of being people-centered, global environmental security, sustained economic prosperity, social justice and harmony and partnership promotion, including a political declaration, 17 overarching goals and 169 specific targets, specific ways of implementation, as well as the follow-up. It is the road map to achieve global sustainable development and meet the requirements of the millennium development goals. This paper summarizes the understanding of the concept of sustainable development from its origin, its significant development, to the proposition and development of the 2030 Agenda for Sustainable Development, and its strategic impact on China.